Answer:
3/2
Step-by-step explanation:
-4-5/4-(-2)
-9/6
3/2
Answer:
A
Step-by-step explanation:
using the rule of logarithms
x = n ⇒ x = ![b^{n}](https://tex.z-dn.net/?f=b%5E%7Bn%7D)
(x + 9) + 3 = 3 ( subtract 3 from both sides )
(x + 9) = 0 , then
x + 9 =
= 1 ( subtract 9 from both sides )
x = - 8
16 + 4x = 10 + 14
16 + 4x = 24.
4x = 24 - 16
4x = 8
x = 8 ÷ 4
x = 2
8x = 2 × 8
8x = 16
Final answer = 16.
Answer:
y=1/3x+4
Step-by-step explanation:
It should be correct as the gradient = 1/3
and the y-intercept = C
= +4